Systematic review of drug–drug interactions between rifamycins and anticoagulant and antiplatelet agents and considerations for management. Issue 4 (28th February 2022) - MacDougall, Conan; Canonica, Theora; Keh, Chris; P. Phan, Binh An; Louie, Janice
Abstract: Rifamycins (rifampin, rifabutin, and rifapentine) play an essential role in the treatment of mycobacterial and some nonmycobacterial infections. They also induce the activity of various drug transporting and metabolizing enzymes, which can impact the concentrations and efficacy of substrates. Many anticoagulant and antiplatelet (AC/AP) agents are substrates of these enzymes and have narrow therapeutic indices, leading to risks of thrombosis or bleeding when coadministered with rifamycins. The objective of this systematic review was to evaluate the effects on AC/AP pharmacokinetics, laboratory markers, and clinical safety and efficacy of combined use with rifamycins. A systematic review following the Preferred Reporting Items for Systematic Reviews and Meta‐analyses guidance was performed. The PubMed, Embase, and Web of Science databases were queried for English‐language reports on combination use of rifamycins and AC/AP agents from database inception through August 2021. The 29 studies identified examined warfarin ( n  = 17), direct oral anticoagulants (DOACs) ( n  = 8), and antiplatelet agents ( n  = 4) combined with rifampin ( n  = 28) or rifabutin ( n  = 1). Eleven studies were case reports or small case series; 14 reported on pharmacokinetic or laboratory markers in healthy volunteers. Rifampin‐warfarin combinations led to reductions in warfarin area under the curve (AUC) of 15%–74%, with variability by warfarin isomer and study. Warfarin dose increases of up to 3–5 times prerifampin doses were required to maintain coagulation parameters in the therapeutic range. DOAC AUCs were decreased by 20%–67%, with variability by individual agent and with rifampin versus rifabutin. The active metabolite of clopidogrel increased substantially with rifampin coadministration, whereas prasugrel was largely unaffected and ticagrelor saw decreases. Our review suggests most combinations of AC/AP agents and rifampin are problematic. Further studies are required to determine whether rifabutin or rifapentine could be safe alternatives for coadministration with AC/AP drugs.